Lectins: a brief review - ESPINO-SOLIS, Gerardo Pavel (Vitae, 2015)
The ability of plant agglutinins to distinguish between erythrocytes of different blood types led Boyd and Shapleigh (1954) to propose for them the name lectins, from the Latin “legere”, to pick out or choose. This term was later generalized to embrace all sugar-specific agglutinins of non-immune origin, irrespective of source and blood type specificity. It was toward the end of the 19th century that evidence first started to accumulate for the presence in nature of proteins possessing the ability to agglutinate erythrocytes. Such proteins were referred to as hemagglutinins, or phytoagglutinins, because they were originally found in extracts of plants. It is generally believed that the earliest description of such a hemagglutinin was by Peter Hermann Stillmark in 1888. This hemagglutinin, which was also highly toxic, was isolated from seeds of the castor tree (Ricinus communis) and was named ricin. Subsequently, H. Hellin demonstrated the presence of another toxic hemagglutinin, abrin, in extracts of the jequirity bean (Abrus precatorius). Well known for being the first to crystallize the enzyme urease, for which he was later awarded the Nobel Prize, James B. Sumner in 1919 isolated from jack bean (Canavalia ensiformis) a crystalline protein that he named concanavalin A, unknowingly obtaining a pure hemagglutinin for the first time. Nearly two decades passed before Sumner and Howel (1936) reported that concanavalin A agglutinates cells such as erythrocytes and yeasts and also precipitates glycogen from solution. They further showed that hemagglutination by concanavalin A was inhibited by sucrose, demonstrating for the first time the sugar specificity of lectins.